2010
DOI: 10.1007/s10342-010-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting understory maximum shrubs cover using altitude and overstory basal area in different Mediterranean forests

Abstract: In some areas of the Mediterranean basin where the understory stratum represents a critical fire hazard, managing the canopy cover to control the understory shrubby vegetation is an ecological alternative to the current mechanical management techniques. In this study, we determine the relationship between the overstory basal area and the cover of the understory shrubby vegetation for different dominant canopy species (Pinaceae and Fagaceae species) along a wide altitudinal gradient in the province of Catalonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 33 publications
5
39
1
Order By: Relevance
“…The "regulating" effect of overstory density on understory has been reported for other forest systems (Bailey & Tappeiner 1998, McKenzie et al 2000, Gracia et al 2007, Coll et al 2011, Botequim et al 2015. Results are also in agreement with the expected dynamics of development of these ecosystems.…”
Section: Relationship Between Stand Density and Understory Vegetationsupporting
confidence: 78%
See 3 more Smart Citations
“…The "regulating" effect of overstory density on understory has been reported for other forest systems (Bailey & Tappeiner 1998, McKenzie et al 2000, Gracia et al 2007, Coll et al 2011, Botequim et al 2015. Results are also in agreement with the expected dynamics of development of these ecosystems.…”
Section: Relationship Between Stand Density and Understory Vegetationsupporting
confidence: 78%
“…2) reveals a tendency similar to that reported for Fw, with the denser stands less prone to present understory vegetation. Other authors have also reported strong negative correlations of canopy cover with understory development, quantified in terms of SDI (McKenzie et al 2000) or stand basal area (Gracia et al 2007, Coll et al 2011, Botequim et al 2015). …”
Section: Relationship Between Stand Density and Understory Vegetationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although shrub recruitment might be nil in Mediterranean forests during very dry years (Mendoza et al, 2009b), it is unlikely that climatic conditions and, specifically, water availability have limited the expansion of shrub communities in the Navahondona forest for at least three reasons. First, results showed that altitude (a proxy of climate) does not influence shrub abundance, i.e.…”
Section: Shrub Composition and Diversitymentioning
confidence: 99%